Paired motor cortex and cervical epidural electrical stimulation timed to converge in the spinal cord promotes lasting increases in motor responses. (20th August 2017) - Mishra, Asht M.; Pal, Ajay; Gupta, Disha; Carmel, Jason B.
Abstract : Key points: Pairing motor cortex stimulation and spinal cord epidural stimulation produced large augmentation in motor cortex evoked potentials if they were timed to converge in the spinal cord. The modulation of cortical evoked potentials by spinal cord stimulation was largest when the spinal electrodes were placed over the dorsal root entry zone. Repeated pairing of motor cortex and spinal cord stimulation caused lasting increases in evoked potentials from both sites, but only if the time between the stimuli was optimal. Both immediate and lasting effects of paired stimulation are likely mediated by convergence of descending motor circuits and large diameter afferents onto common interneurons in the cervical spinal cord. Abstract: Convergent activity in neural circuits can generate changes at their intersection. The rules of paired electrical stimulation are best understood for protocols that stimulate input circuits and their targets. We took a different approach by targeting the interaction of descending motor pathways and large diameter afferents in the spinal cord. We hypothesized that pairing stimulation of motor cortex and cervical spinal cord would strengthen motor responses through their convergence. We placed epidural electrodes over motor cortex and the dorsal cervical spinal cord in rats; motor evoked potentials (MEPs) were measured from biceps. MEPs evoked from motor cortex were robustly augmented with spinal epidural stimulation delivered at an intensity below the threshold for provoking an MEP. Augmentation was critically dependent on the timing and position of spinal stimulation. When the spinal stimulation was timed to coincide with the descending volley from motor cortex stimulation, MEPs were more than doubled. We then tested the effect of repeated pairing of motor cortex and spinal stimulation. Repetitive pairing caused strong augmentation of cortical MEPs and spinal excitability that lasted up to an hour after just 5 min of pairing. Additional physiology experiments support the hypothesis that paired stimulation is mediated by convergence of descending motor circuits and large diameter afferents in the spinal cord. The large effect size of this protocol and the conservation of the circuits being manipulated between rats and humans makes it worth pursuing for recovery of sensorimotor function after injury to the central nervous system. Key points: Pairing motor cortex stimulation and spinal cord epidural stimulation produced large augmentation in motor cortex evoked potentials if they were timed to converge in the spinal cord. The modulation of cortical evoked potentials by spinal cord stimulation was largest when the spinal electrodes were placed over the dorsal root entry zone. Repeated pairing of motor cortex and spinal cord stimulation caused lasting increases in evoked potentials from both sites, but only if the time between the stimuli was optimal. Both immediate and lasting effects of paired stimulation are likely mediated by convergence of descending motor circuits and large diameter afferents onto common interneurons in the cervical spinal cord.